THE CONSTANCY OF UPPER MANTLE FO2 THROUGH TIME INFERRED FROM V/SC RATIOS IN BASALTS - Anser Li Z.-X.; Aeolus Lee C.-T. (My University, 2004)
The geochemical behaviors of V and Sc during partial melting are more similar to each other than to most other elements but, in detail, the partitioning of V is redox-sensitive whereas that of Sc is not. The V/Sc ratio in basalts is shown here to be a sensitive and robust recorder of the oxygen fugacity (fO2) of their mantle source regions. The use of V/Sc ratios differs from the use of V and/or Cr elemental systematics in basalts because the latter, strictly speaking, provide information on the fO2 of the erupted magma and not necessarily that of the mantle source. V/Sc ratios on the other hand can “see through” magmatic differentiation processes, such as olivine crystallization, and therefore, provide a better memory of the fO2 of the mantle. The V/Sc ratios of mid-ocean ridge basalts (MORBs) are shown here to average 6.74±1.11 (1σ), which constrains the fO2 of the modern mantle to roughly 0.3±0.5 (1σ) log units below the fayalite–magnetite–quartz (FMQ) buffer. Archean basalts (up to 3.5 Ga) are shown to have identical V/Sc ratios (6.34±0.62, 1σ) to within error indicating that the fO2 of the mantle source to Archean basalts differ from that of modern convecting mantle by no more than 0.3 log unit. The constraints based on V/Sc systematics represent an improvement on studies using V or Cr elemental systematics, which constrain the fO2 of Archean and modern mantles to be identical, but only to within ±0.5 to 1 log unit. These observations show that there has been little or no secular evolution of the fO2 of the upper mantle, at least since the early Archean.